A positive linear association between uric acid and the risk of gestational diabetes mellitus: a single-center retrospective study - Zhang, Mengfan; Li, Chunbo; Zhao, Xiaoli; Li, Mengchun; Tian, Zhaohua (Frontiers in Endocrinology, 2026)
ObjectiveThis study aimed to examine the association between maternal uric acid (UA) concentrations measured prior to 24 weeks of pregnancy and the risk of gestational diabetes mellitus (GDM) between 24 and 28 weeks.MethodsIn this retrospective cohort conducted at a single institution, 847 expectant mothers receiving prenatal services at Zhengzhou People’s Hospital from August to December 2024 were enrolled. All participants had their UA levels measured prior to 24 gestational weeks, followed by a 75 g oral glucose tolerance assessment conducted between weeks 24 and 28. Multivariable logistic regression analysis was performed to evaluate the association between UA levels and the risk of GDM, supplemented by subgroup analysis, sensitivity analysis, and analytical procedures including receiver operating characteristic (ROC) curve evaluation and modeling with restricted cubic spline (RCS).ResultsAmong 847 enrolled pregnancies, the proportion with GDM was 21.1% (n = 179). Multivariate logistic regression showed that each 1 µmol/L or each one-standard-deviation elevation in serum UA corresponded to a markedly greater risk of GDM (OR: 1.005, 95% CI: 1.001–1.009; OR: 1.274, 95% CI: 1.062–1.528, respectively). In comparison to the lowest UA tertile (T1), T2 and T3 exhibited elevated risk for GDM, with ORs of 1.976 (95% CI: 1.203–3.247) and 2.468 (95% CI: 1.520–4.007), respectively. Subgroup analyses revealed that in women aged > 30, with gravidity < 2, parity < 2, or body mass index before conception below 24 kg/m2, both continuous and categorical UA demonstrated a clear and statistically meaningful association with GDM. Sensitivity analyses supported consistent results, with both median- and quartile-based groupings showing a significant association between higher UA levels and greater GDM risk (P < 0.05). ROC curve analysis suggested that serum UA provided limited yet statistically significant discriminative information for GDM (AUC = 0.623). RCS modeling revealed a notable positive linear association between UA concentrations and the risk of GDM (P for nonlinearity = 0.140).ConclusionHigher maternal serum UA measurements taken prior to 24 gestational weeks were strongly linked to GDM risk during weeks 24–28.